Effects of N6-benzylaminopurine and Indole Acetic Acid on In Vitro Shoot Multiplication, Nodule-like Meristem Proliferation and Plant Regeneration of Malaysian Bananas (Musa spp.) - Philip Sipen; Michael R Davey (Tropical Life Sciences Research, 2012)
Different concentrations of N6-benzylaminopurine (BAP) and indole acetic acid (IAA) in Murashige and Skoog based medium were assessed for their effects on shoot multiplication, nodule-like meristem proliferation and plant regeneration of the Malaysian banana cultivars Pisang Mas, Pisang Nangka, Pisang Berangan and Pisang Awak. BAP at 1–14 mg L–1 with or without 0.2 mg L–1 IAA, or BAP at 7–14 mg L–1 with the same concentration of IAA, was evaluated for shoot multiplication from shoot tips and the proliferation of nodule-like meristems from scalps, respectively. Plant regeneration from scalps was assessed using 1 mg L–1 BAP and 0.2 mg L–1 IAA separately, or a combination of these two growth regulators. Data on shoot multiplication, the proliferation of nodule-like meristems with associated plant regeneration were recorded after 30 days of culture. A maximum of 5 shoots per original shoot tip was achieved on medium supplemented with BAP at 5 mg L–1 (Pisang Nangka), 6 mg L–1 (Pisang Mas and Pisang Berangan), or 7 mg L–1 (Pisang Awak), with 0.2 mg L–1 IAA. BAP at 11 mg L–1 with 0.2 mg L–1 IAA induced the most highly proliferating nodule-like meristems in the four banana cultivars. Plant regeneration from scalps was optimum in all cases on medium containing 1 mg L–1 BAP and 0.2 mg L–11 IAA. This is the first report on the successful induction of highly proliferating nodule-like meristems and plant regeneration from scalps of the Malaysian banana cultivars Pisang Mas, Pisang Nangka, Pisang Berangan and Pisang Awak. Kepekatan berbeza N6-benzylaminopurine (BAP) dan asid indole asetik (IAA) dalam medium Murashige dan Skoog telah dikaji kesannya terhadap penggandaan pucuk, proliferasi bintil meristem dan penjanaan semula pokok pisang Malaysia, kultivar Pisang Mas, Pisang Nangka, Pisang Berangan dan Pisang Awak. BAP pada 1–14 mg L–1 dengan atau tanpa 0.2 mg L–1 IAA, atau BAP pada 7–14 mg L–1 dengan kepekatan IAA yang sama telah dikaji untuk penggandaan pucuk dan proliferasi bintil meristem masingmasing. Penjanaan semula dari scalp telah dinilai menggunakan 1 mg L–1 BAP dan 0.2 mg L–1 IAA berasingan ataupun dalam kombinasi kedua-dua pengawal atur pertumbuhan tersebut. Data penggandaan pucuk, proliferasi bintil meristem dengan penjanaan semula pokok telah direkodkan selepas pengkulturan selama 30 hari. Maksimum 5 pucuk untuk setiap pucuk asal telah dicapai dalam medium yang dibekalkan dengan BAP pada 5 mg L–1 (Pisang Nangka), 6 mg L–1 (Pisang Mas and Pisang Berangan), atau 7 mg L–1 (Pisang Awak), dengan 0.2 mg L–1 IAA. BAP pada 11 mg L–1 dengan 0.2 mg L–1 IAA telah menghasilkan bintil meristem yang proliferasi paling banyak dalam empat kultivar pisang. Penjanaan semula dari scalp optimum dalam semua kes dengan medium yang mengandungi 1 mg L–1 BAP dan 0.2 mg L–1 IAA. Ini merupakan laporan pertama tentang induksi berjaya bintil meristem dan penjanaan semula pokok dari scalp kultivar pokok pisang Malaysia iaitu Pisang Mas, Pisang Nangka, Pisang Berangan dan Pisang Awak.